A Society that Counts to Two Again - Khazieva, Nataliia O. (International Journal of Criminology and Sociology, 2022)
The place of research object will be taken by the digital society and man belonging to this era. Between the researcher and the object under study (digital society, modern man) there will be a prism through which it will be possible to consider the problems of interest to us and we will be able to discern the prism of research better. This position of the observer, as well as the means and methods of observation, will help us look differently at the object of our interest: changes in a society driven by digitalization, the role of numbers in modern society, and the updated properties of a digit.